Growth of wrinkle-free and ultra-flat Bi-layer graphene on sapphire substrate using Cu sacrificial layer. (31st August 2021) - Lou, Gang; Ouyang, Yi; Xie, Ying; Wang, Wei; Liu, Zhaoping
Abstract: The transfer process of chemical vapor deposition graphene film leads to unavoidable crack, wrinkles, doping, and contamination, which limits its function to establish stable and high-performance devices. It raises a growing interest to fabricate high-quality graphene on the target substrate directly. Here, bi-layer graphene (BLG) film can be grown on sapphire substrate by a Cu sacrificial layer using atmospheric-pressure chemical vapor deposition. The as-obtained BLG at the interface between sapphire and Cu layer is free of wrinkles, and the corresponding surface roughness Ra is as low as 0.66 nm. The square resistance of the graphene is 898.1 ohm sq −1, which is the lowest among the records of graphene film directly grown on nonmetal substrates.